Mengenali Isu Strategis Pengembangan Kawasan Desa Wisata Edukasi Kopi Rasagalor, Kabupaten Bandung - Widagdo, Rama Arianto; Weishaguna; Burhanudin, Hani; Saraswati; Asyiawati, Yulia; Barwanto, Lutfhi Ahmad; Pratama, Aldy; Ferbiyandani, Mochamad Rifky; Nurhasanah, Halimah; Serdani, Sherly Defannya (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
Determining the correct strategic issues when developing an area is crucial so that the solution can effectively be implemented to the existing dynamics. Unfortunately, determining strategic issues is often disregarded or not taken seriously during the planning process. A Similar mistake of not defining strategic issues appropriately looms over the development of Mekarmanik Village, which is based on the Rasagalor Coffee Educational Tourism Concept. This research aims to understand the development dynamics happening in Mekarmanik Village so that the correct issue could be determined. By using data and information gathered from literature studies, focus group discussions, and field observations two types of analysis were done to correctly determine strategic issues that fit with the existing condition of Mekarmanik Village, namely case study, content analysis, and descriptive analysis. The result shows that the strategic issues of developing Mekarmanik Village as a tourism village are specific education, tourism concept exploration, and physical infrastructure improvement.